Measurement of the absolute branching fractions for D−s→ℓ−v̄ℓ and extraction of the decay constant fDs - Amo Sanchez, Pablo del; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich; Hartmann, Thomas; Leddig, Torsten; Schröder, Henning; Waldi, Roland (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
The absolute branching fractions for the decays D−s→ℓ−¯νℓ (ℓ=e, μ, or τ) are measured using a data sample corresponding to an integrated luminosity of 521 fb−1 collected at center-of-mass energies near 10.58 GeV with the BABAR detector at the PEP-II e+e− collider at SLAC. The number of D−s mesons is determined by reconstructing the recoiling system DKXγ in events of the type e+e−→DKXD*−s, where D*−s→D−sγ and X represents additional pions from fragmentation. The D−s→ℓ−νℓ events are detected by full or partial reconstruction of the recoiling system DKXγℓ. The branching fraction measurements are combined to determine the D−s decay constant fDs=(258.6±6.4±7.5) MeV, where the first uncertainty is statistical and the second is systematic.
Gesehen am 23.08.2023
Im Titel ist "function" als mathematisches Zeichen dargestellt
Im Titel steht der Buchstabe "v" mit einem Oberstrich
BABAR Collaboration: P. del Amo Sanchez, A. Adametz, J. Marks, U. Uwer, T. Hartmann, T. Leddig, H. Schröder, R. Waldi [und viele weitere]